Development of Team Cohesiveness Measurement Instruments in Interprofessional Collaborative Practice in Health Care - francisca sri susilaningsih; Henny Suzana Mediani; Titis Kurniawan (JKP (Jurnal Keperawatan Padjajaran), 2018)
Abstract